Perancangan Modul Keamanan Website dan Basis Data dalam Lingkup Sistem Terdistribusi dengan Strategi Pembelajaran Berbasis Case Method - Hartini Ramli; Muh. Yasin Kadir; Husnul Hatima; Juliano Nufiansyach Dini; Reyna Buryani Al'Safinat.R; Reynaldi Nafzal Azhari (PT. Global Research Collaboration, 2025)
In today's digital era, information systems have evolved from centralized models to distributed systems that span across various platforms and geographic locations. While this transformation enhances efficiency and scalability, it also increases security risks, particularly concerning websites and databases, which are core components of digital services. This module is designed to provide in-depth understanding of information security within distributed systems, focusing on the protection of websites and databases. The learning approach applies the case method, placing students in real or simulated scenarios to analyze, solve problems, and design security solutions based on the principle of defense in depth. This module aims to enhance students' critical thinking and technical skills in addressing ever-evolving information system security threats.